2018
DOI: 10.30651/jkm.v2i2.940
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Teori Self Care Orem’s Dan Teori Becoming A Mother Mercer’s Pada Ibu Post Seksio Sesaria Usia Remaja : Laporan Kasus

Abstract: AbstrakPersalinan seksio sesaria merupakan salah satu alternatif persalinan yang mengalami peningkatan dari tahun ke tahun. Masalah fisik dan psikologis lebih sering muncul pada ibu post partum dengan persalinan seksio sesaria. Keluhan fisik dan psikologis post seksio sesaria tersebut dirasakan lebih berat oleh ibu-ibu usia remaja. Dukungan perawat maternitas penting untuk membantu ibu post seksio cesarea usia remaja dalam memenuhi kebutuhan dasarnya dan dapat beradaptasi dengan peran baru sebagai ibu. Teori s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…A study of Rahmayanti showed on Idaman Banjarbaru Hospital, there were 70% of pregnant women in the third trimester had low sleep quality. Tiredness in the day time, yawning frequently and periorbital dark circles was commonly found (Rahmayanti, 2018). Wulandari and Wantini described most of pregnant women (76,2%) had difficulty on falling asleep, 73% had to wake up to go to the toilet more than three times a week, 71,4% had uncomfortable sleep hygiene more than three time a week (Wulandari & Wantini, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study of Rahmayanti showed on Idaman Banjarbaru Hospital, there were 70% of pregnant women in the third trimester had low sleep quality. Tiredness in the day time, yawning frequently and periorbital dark circles was commonly found (Rahmayanti, 2018). Wulandari and Wantini described most of pregnant women (76,2%) had difficulty on falling asleep, 73% had to wake up to go to the toilet more than three times a week, 71,4% had uncomfortable sleep hygiene more than three time a week (Wulandari & Wantini, 2020).…”
Section: Introductionmentioning
confidence: 99%